Self-collected and clinician-collected anal swabs show modest agreement for HPV genotyping. - Racheal S Dube Mandishora; Trine B Rounge; Megan Fitzpatrick; Irene Kraus Christiansen; Ole Herman Ambur; Sonja Lagström; Babill Stray-Pedersen; Massimo Tommasino; Joel Palefsky; Zvavahera M Chirenje (PLoS ONE)
Background & aim Women with HIV/HPV coinfection and cervical lesions are at increased risk of developing HPV related anal cancer. Self-collection of anal swabs may facilitate HPV molecular testing in anal cancer screening, especially in high-risk groups, and yet it is not adequately studied. We evaluated level of agreement between self-collected anal swabs (SCAS) and clinician-collected anal swabs (CCAS) when used for HPV genotyping. We also described the anal HPV genotype distribution and HIV/HPV coinfection. Methods We performed a cross sectional study with participants from a visual-inspection-with-acetic-acid and cervicography (VIAC) clinic, in Harare, Zimbabwe. In a clinic setting, the women aged ≥18 years provided anal swabs in duplicate; first CCAS and then SCAS immediately after. HPV detection and genotyping were performed using next generation amplicon sequencing of a 450bp region of the HPV L1 gene. Level of agreement of HPV genotypes between CCAS and SCAS was calculated using the kappa statistic. McNemar tests were used to evaluate agreement in the proportion of genotypes detected by either method. Results Three-hundred women provided 600 samples for HPV genotyping. HPV genotypes were detected in 25% of SCAS and in 22% of CCAS. The most common genotypes with CCAS were HPV52, HPV62 and HPV70 and with SCAS were HPV62, HPV44, HPV52, HPV53 and HPV68. Total HPV genotypes detected in CCAS were more than those detected in SCAS, 32 versus 27. The agreement of HPV genotypes between the two methods was 0.55 in kappa value (k). The test of proportions using McNemar gave a Chi-square value of 0.75 (p = 0.39). Multiple HPV infections were detected in 28/75 and 29/67 women for CCAS and SCAS respectively. Conclusions SCAS and CCAS anal swabs showed moderate agreement, with no statistically significant difference in the proportion of genotypes detected by either methods. Although the differences between the two methods were not statistically significant, CCAS detected more HPV genotypes than SCAS and more HPV infections were detected in SCAS than in CCAS. Our data suggest that self-collected anal swabs can be used as an alternative to clinician-collected anal swabs for HPV genotyping.